The Relationship Of Knowledge, Attitudes And Actions With Medication Adherence In Pulmonary Tuberculosis Patients At The Pulmonary Polyclinic Of Subulussalam City Hospital - Nursa'adah Cibro; Safrizal Safrizal; Eva Flourentina Kusumawardani; Maiza Duana; Lili Eky Nursia N (International Journal of Public Health, 2024)
Tuberculosis (TB) was still a global challenge in the world of health and required special attention to increase the level of patient compliance with treatment. This study aimed to explore the relationship between patient knowledge, attitudes, and actions and the level of adherence to taking medication in TB patients at the Pulmonary Polyclinic of Subulussalam City Hospital. The study used an observational analytical design with a cross-sectional approach. The research population involved all TB patients undergoing treatment at Subulussalam City Hospital, with a sample of 76 respondents selected through accidental sampling. Data were collected through interviews using the MMAS-8 questionnaire, and data analysis was carried out using the chi-square test. The majority of respondents showed a high level of knowledge (47.37%), poor attitudes (59.21%), and good actions (64.47%), but the level of compliance was low (46.05%). Statistical analysis showed that there was a significant relationship between knowledge (p=0.000), attitudes (p=0.014), and actions (p=0.010) with the level of adherence to taking medication. The knowledge, attitudes, and actions of TB patients at the Lung Polyclinic of Subulussalam City Hospital had a significant effect on their level of compliance in taking medication. Efforts were needed to increase patient understanding and special approaches to increase compliance to support the success of TB therapy.